THE STRUCTURAL ENVIRONMENTS OF TRACE ELEMENTS IN DRY AND HYDROUS SILICATE GLASSES; A MANGANESE AND STRONTIUM K-EDGE X-RAY ABSORPTION SPECTROSCOPIC STUDY - Kohn S.C.; Charnock J.M.; Henderson C.M.B.; Greaves G.N. (My University, 1990)
The structural environments of Mn2+ and Sr2+ at concentrations of 0.2–0.8 wt% in dry and hydrous silicate glasses have been studied using X-ray absorption spectroscopy (EXAFS and XANES). The environment of Mn in hydrous silica glasses containing 4.5 and 6.0 wt% H2O appears to be close to an undistorted octahedral site, whereas Mn in other compositions, both dry and hydrous, occupies either a distribution of octahedral and tetrahedral sites, or distorted, non-centrosymmetric sites. The fraction of non-centrosymmetric sites (including tetrahedral) or the average degree of distortion of the sites decreases with both increasing dissolved water concentration and number of non-bridging oxygens in the glass. For Sr the changes as a function of polymerisation and water concentration are less clear, but it appears that the average Sr-O distances are shorter than in crystalline silicates and decrease further with decreasing polymerisation. The structural data obtained in this study are not readily integrated with previous partitioning data for Mn, suggesting that changes in the first-shell coordination geometry of Mn do not play a direct role in controlling the melt compositional dependence of trace element partition coefficients. It is tentatively suggested that distortions of the framework resulting from the incorporation of Mn (i.e. a second shell effect) control the partitioning behaviour.